GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KINERJA KEUANGAN BANK SYARIAH - M. Pudail; Yeny Fitriyani; Achmad Labib (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The existence of interest between principal and agent, hence arises a conflict of interest in management of Syria bank. In order to minimize the conflict, the implementation of GCG can be one of the solutions. Implementation of GCG, which is done consistently and continuously in the end can improve the financial performance of sharia banks. The type of this study is the study of causality with quantitative approach. The number of samples in the study was 13 sharia banks with documentation as their data collection method. Data analysis technique in this research is using a panel data regression method with the help of software Evies version 9. The result of this research indicates that GCG implementation has significant influence to NPF, ROA, and BOPO. The implementation of GCG in this study proved to have no effect on ROE and FDR.